Analisis Faktor-Faktor yang Memengaruhi Perolehan Surplus Underwriting pada Asuransi Jiwa Syariah di Indonesia (Periode 2015-2020) - Amelia Nadiah Wahyu Putri; Jaenal Effendi (Department of Islamic Economics, IPB University, 2021)
In Islamic insurance, if at the end of the period there is a surplus from the substraction result between total insurance income in the tabarru’ fund and insurance expenses, the surplus will be called as underwriting surplus. A good Islamic insurance company can be seen when the company succeeds in obtaining an underwriting surplus, because it is a proof when the company has managed the participant funds well. The underwriting surplus can be used as a reserve fund when an underwriting deficit occurs or when insurance expenses exceed insurance income, thereby it can improve the public interest in Islamic insurance. Therefore, this study aims to analyze the development of the underwriting surplus in Islamic life insurance in Indonesia and the factors that influence it by using panel data regression method. The estimation results using the REM model show that the variables of total assets and GDP have a positive and significant effect. Meanwhile, the contribution allowance, claim allowance, and inflation variables have a negative and significant effect.